(untitled) (World Bulletin of Education and Learning, 2025)
The article examines the methodological foundations of organizing interdisciplinary integration within individualized education, with a special focus on its relevance for musical education in higher pedagogical institutions. The study analyzes how interdisciplinary approaches enhance learners’ cognitive engagement, creative thinking, and personalized learning trajectories by connecting knowledge, skills, and competencies across various academic domains. Individualized education is viewed as a flexible pedagogical model that prioritizes learner autonomy, differentiated instruction, and adaptive learning pathways tailored to students’ interests, abilities, and professional needs. Within this model, interdisciplinary integration serves as a key mechanism for enriching the educational process, promoting deeper conceptual understanding, and fostering holistic development. The research highlights the pedagogical, psychological, and methodological principles that guide the design and implementation of interdisciplinary learning experiences, especially in the context of musical training where creative, analytical, digital, and reflective competencies intersect. The study further evaluates the role of digital technologies, project-based learning, cross-disciplinary collaboration, and competency-based assessment in supporting individualized and integrated learning environments. The findings emphasize that effective interdisciplinary integration contributes to improved learner motivation, enhanced academic performance, and the development of transferable skills essential for professional growth in the field of musical education.